Chronic ethanol exposure alters prelimbic prefrontal cortical Fast-Spiking and Martinotti interneuron function with differential sex specificity in rat brain. (1st January 2020) - Hughes, Benjamin A.; Crofton, Elizabeth J.; O'Buckley, Todd K.; Herman, Melissa A.; Morrow, A. Leslie
Abstract: Chronic ethanol exposure results in numerous neurobiological adaptations that promote deficits in medial prefrontal cortical (mPFC) function associated with blunted inhibitory control and elevated anxiety during withdrawal. Studies exploring alcohol dependence-related changes in this region have largely investigated adaptations in glutamatergic signaling, with inhibitory neurotransmission remaining relatively understudied. To address this, we used biochemical and electrophysiological methods to evaluate the effects of ethanol on the activity of deep-layer prelimbic mPFC Fast-Spiking (FS) and Martinotti interneurons after chronic ethanol exposure in male and female rats. We report that chronic alcohol exposure significantly impairs FS neuron excitability in both males and females. Interestingly, we observed a marked sex difference in the baseline activity of Martinotti cells that furthermore displayed differential sex-specific responses to alcohol exposure. In addition, alcohol effects on Martinotti neuron excitability negatively correlated with hyperpolarization-activated currents mediated by hyperpolarization-activated cyclic nucleotide gated (HCN) channels, indicative of a causal relationship. Analysis of HCN1 protein expression also revealed a substantial sex difference, although no effect of ethanol on HCN1 protein expression was observed. Taken together, these findings further elucidate the complex adaptations that occur in the mPFC after chronic ethanol exposure and reveal fundamental differences in interneuron activity between sexes. Furthermore, this disparity may reflect innate differences in intracortical microcircuit function between male and female rats, and offers a tenable circuit-level explanation for sex-dependent behavioral responses to alcohol. Highlights: Chronic alcohol exposure blunts Layer V fast-spiking interneuron activity in prefrontal cortex. Alcohol differentially affects Martinotti interneuron excitability between sexes. Effects on Martinotti cell function appear to be due to altered expression of HCN channels.